An Anthropological Study of COVID-19: Effects on Socio-cultural Life of the People - Sapkota, Prakash Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2020)
The disease is such a situation in the body of the people which adversely affect physical, mental, and the social situation remains. This situation appears with an imbalance relation between human's particular biology and his environment. The germ theory of disease trusts scientific theory for the multitude of disease caused by the activities of microorganisms. Coronavirus, too small microorganism cause COVID-19 disease in people. In this paper, an attempt has been made to understand the coronavirus and its effects on the socio-cultural life of the people based on the non-participatory observation and available literature by using descriptive research design. From this study it can be said that, coronavirus caused COVID-19 disease in the respiratory organ of people which is the most sensitive part of the body to alive. Coronavirus has increased fear among the people across the world which directly affects all socio-cultural dimension as educational, economic, inequality and domestic violence, cultural, religious, risk perception, and suicide activities of people. In this situation, it is better to focus on personal safety, complete social responsibility, develop knowledge and skills on both indigenous and modern medicine to cure and protect from such types of pandemic diseases based on their ecological environment.